Credit risk frontiers : subprime crisis, pricing and hedging, CVA, MBS, ratings, and liquidity - Bielecki, Tomasz R., 1955-; Brigo, Damiano, 1966-; Patras, Frederic (Hoboken, NJ : Wiley, 2011)
'A timely guide to understanding and implementing credit derivatives Credit derivatives are here to stay and will continue to play a role in finance in the future. But what will that role be? What issues and challenges should be addressed? And what lessons can be learned from the credit mess? Credit Risk Frontiers offers answers to these and other questions by presenting the latest research in this field and addressing important issues exposed by the financial crisis. It covers this subject from a real world perspective, tackling issues such as liquidity, poor data, and credit spreads, as well as the latest innovations in portfolio products and hedging and risk management techniques. Provides a coherent presentation of recent advances in the theory and practice of credit derivatives. Takes into account the new products and risk requirements of a post financial crisis world. Contains information regarding various aspects of the credit derivative market as well as cutting edge research regarding those aspects. If you want to gain a better understanding of how credit derivatives can help your trading or investing endeavors, then Credit Risk Frontiers is a book you need to read.'--
Includes bibliographical references and index.
Keywords: Credit derivatives -- United States; Global Financial Crisis, 2008-2009